Abdominal Aortic Aneurysms: Epidemiological, Clinical and Echographic Aspects in The Health Structures of Lomé and At The Kara University Hospital (TOGO) - Machihude, PIO; Abalo, Mario BAKAI; Bénédict, SOUHO; Edabi, OTOYI; Kpatekana, SIMLAWO; Borgotia, D. ATTA; Tchaa, TCHEROU; Yaovi, Mignazonzon AFASSINOU; Lihanimpo, DJALOGUE; D, Wiyaou Dieu-Donné KAZIGA; Soulemane, PESSINABA (Journal of Hypertension and Cardiology, 2023)
Objective To describe the epidemiological, clinical and arterial Doppler ultrasound aspects of abdominal aortic aneurysm (AAA). Material and Methods This is a prospective study with descriptive and analytical aims carried out from January 2019 to March 2022 (3 years) at the cardiovascular exploration center (CEC) "Saint-Esprit" of the association of the people's doctors for the research on cardiovascular diseases (AMP-MCV), at the clinic "Le Printemps" and at the University Hospital of Kara. All patients who underwent arterial Doppler ultrasound of the lower limbs for any reason in these centers during the study period were included. Ultrasound scans were performed or confirmed by a physician with a diploma specializing in vascular Doppler ultrasound. Results We retained 32 Doppler ultrasound scans out of 739 performed for AAA with a frequency of 4.38%. The mean age was 73.5± 9.07 years. The sex ratio M/F was 1.4. The cardiovascular medical history (84.38%) found was: hypertension (33.33%), diabetes (18.52%), dyslipidemia (33.33%) and a combination of diabetes and hypertension (14.81%). The circumstances of discovery were: downstream MI ischemia (72%), incidental finding on abdominal ultrasound (15.63%) and De bakey sign (6.25%). The location of the aneurysms was subrenal (84.4%), suprarenal (9.4%) and both (6.2%). AAAs were fusiform (71.9%) and saccular (28.1%). The size of the aneurysms was greater than 5 cm in 78.17% of patients. High blood pressure increases the probability of the occurrence of subrenal AAA while dyslipidemia increases the occurrence of fusiform AAA. Diabetes increases the probability of occurrence of AAA larger than 7cm. AAAs were thrombosed in 75% of patients. There were extensions of the aneurysms to the iliac arteries in 70.59%. Downstream embolic complications represented 46.88%, in the form of occlusions and tight stenoses. Spontaneous mortality was 81.24%. Conclusion Arterial Doppler ultrasonography is a very important tool in the screening, positive and lesion diagnosis of AAA. The risk factors for AAA are: age over 60 years, male gender, hypertension, diabetes and dyslipidemia. Early detection remains essential, because the spontaneous prognosis is poor.
Keywords: aneurysms; abdominal aorta; arterial Doppler ultrasound; Togo